The role of GRI standards in reporting the dimensions of sustainable development - An applied study in a number of local companies on the Iraq Stock Exchange - Al-Shammari, Suaad Adnan Noaman (Journal of Economics and Administrative Sciences, 2022)
The current research aims to shed light on the Global Reporting Initiative (GRI), which helps to report financial and non-financial information by economic units in general and listed on the Iraq Stock Exchange in particular. The research was based on a main premise that apply the criteria of the Global Reporting Initiative (GRI) would provide useful information to users to help them make appropriate decisions. To achieve the goal of the research, the descriptive analysis method was used, and quantitative analysis was used. At the level of the descriptive analysis method, a desk survey was conducted. As for the quantitative analysis, it relied on applied data through a questionnaire form (Questioners) as a research tool, and the Statistical Package for Social Sciences (spss) was used to analyze the research data and to reach the results. The research got a set of conclusions, the most important of which is that the accounting profession seeks to provide all information that is useful to users in the process of making appropriate decisions. Therefore the application of the Global Reporting Initiative would improve the quality of the information supplied to users as well as economic help units to Think about its strategy, manage risks, and provide a comprehensive picture of the performance of economic units Yeh. Based on the conclusions, a set of recommendations were presented, the most important of which was the need to prepare requirements and qualifications that help implement the Global Reporting Initiative by units to ensure the provision of information that is useful to users in the decision-making process. He urged economic units to submit reports through the application of the Global Reporting Initiative to improve the quality of information provided to users on the one hand and the possibility of improving the unit’s performance on the other hand